Health Law Reform in Ensuring Doctor Competence Based on the Integration of Ethics, Discipline and Science for Global Welfare - Rika Noviantini; Hidayati Hidayati (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Doctors play a crucial role in determining the quality of healthcare services and in upholding the right to health as guaranteed by the constitution and international human rights frameworks. Despite this essential role, medical practice continues to encounter significant challenges, including disparities in medical education quality, inadequate competency assessment mechanisms, and limited integration of professional ethics, discipline, and scientific standards within the health legal system. These issues create risks to patient safety and undermine public trust in medical services. This research analyzes the urgency of health law reform to ensure physician competence and proposes an integration model that unites ethics, discipline, and scientific foundations as the core pillars for equitable and welfare-oriented medical professional governance. Using a normative legal research method, this study adopts legislative, conceptual, and comparative approaches. Primary and secondary legal materials are examined qualitatively through doctrinal studies, normative analysis, and comparisons with governance practices of the medical profession in other countries. The study finds that health law reform should prioritize strengthening regulations on competency standards, transparent certification and periodic recertification systems, as well as integrated professional oversight that aligns ethics, discipline, and legal accountability. The proposed integration model serves as a framework to ensure that every physician maintains measurable competence, adheres to professional ethics, and upholds clear legal responsibilities in clinical practice. Reforming health law through such integration is a strategic step to enhance medical service quality, reinforce patient protection, and advance global justice and welfare.